2001
DOI: 10.1063/1.1383270
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in ultrathin artificial cuprate structures

Abstract: Layer-by-layer pulsed-laser deposition has been used to grow ultrathin superconducting (Ba0.9Nd0.1)CuO2+x/CaCuO2 artificial structures with various thicknesses of the two constituent layers. Superconductivity was observed in the ultrathin structure consisting of a single CaCuO2 superconducting block sandwiched between two (Ba0.9Nd0.1)CuO2+x blocks. The results obtained allowed an experimental demonstration of the currently accepted structural model for high TC superconductivity, which requires the presence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Details of the growth process are reported in Ref. 11. Such heterostructures consist of N CaCuO 2 unit cells, sandwiched between M layers of Ba 0.9 Nd 0.1 CuO 2ϩx ͑namely, the CR block͒.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the growth process are reported in Ref. 11. Such heterostructures consist of N CaCuO 2 unit cells, sandwiched between M layers of Ba 0.9 Nd 0.1 CuO 2ϩx ͑namely, the CR block͒.…”
mentioning
confidence: 99%
“…7,8 Following this approach, it has been demonstrated that a single IL block is the minimal structural requirement for high T c superconductivity. [9][10][11] Because of the high oxygen pressure used during film deposition, direct calibration of the deposition rate by monitoring the intensity oscillations of the reflection high-energy electron diffraction ͑RHEED͒ spots is not possible. Precise calibration of the growth rates can be obtained a posteriori by both x-ray diffraction ͑XRD͒ and x-ray reflection ͑XRR͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two sintered powder targets, with a nominal composition of Ba 0:9 Nd 0:1 CuO 2 and CaCuO 2 , mounted on a multitarget system, were used. The substitution of 10% of the Ba atoms with trivalent Nd cations, even if not strictly necessary for superconductivity [11,12], helped us to find the right growth conditions by slightly decreasing the uncompensation of the electrical charge in the CR block. The growth temperature was about 640 C and the molecular oxygen pressure was 1 mbar.…”
mentioning
confidence: 99%
“…They consist of one superconducting infinite layer block (two CaCuO 2 unit cells), sandwiched between two charge reservoirs (5 Ba-based unit cells). The structure was grown on (001) SrTiO 3 substrates, with nominally zero miscut angle, by using a focussed KrF excimer pulsed laser source [4,5]. The films were photolithographically patterned into bridges.…”
mentioning
confidence: 99%